1978
DOI: 10.1111/j.1476-5381.1978.tb17276.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Production by Macrophages and the Effect of Anti‐inflammatory Drugs

Abstract: Macrophages derived from peritoneal cavity inflammatory exudates of guinea‐pigs produced substantial amounts of prostaglandin E2‐like activity during in vitro culture, so providing the basis for an experimental model of prostaglandin production during inflammatory reactions. Dose‐related inhibition of prostaglandin biosynthesis was demonstrated by 16 acidic non‐steroidal anti‐inflammatory drugs. Seven anti‐inflammatory glucocorticosteroid preparations inhibited prostaglandin production in a dose‐related manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…Other work from our laboratory has demonstrated that monocytes directly resorb both devitalized bones by a mechanism which is not mediated by the action of osteoclasts (25) and live bones through an osteoclast-mediated mechanism which is prostaglandin-dependent (26). There is also other evidence which suggests that monocytes and macrophages synthesize and release PGs (27)(28)(29), collagenase (30), and hydrolytic enzymes (31), which are all capable of resorbing bone or degrading bone matrix. It is also possible that circulating mononuclear cells may transform or differentiate into osteoclasts (32).…”
Section: Discussionmentioning
confidence: 99%
“…Other work from our laboratory has demonstrated that monocytes directly resorb both devitalized bones by a mechanism which is not mediated by the action of osteoclasts (25) and live bones through an osteoclast-mediated mechanism which is prostaglandin-dependent (26). There is also other evidence which suggests that monocytes and macrophages synthesize and release PGs (27)(28)(29), collagenase (30), and hydrolytic enzymes (31), which are all capable of resorbing bone or degrading bone matrix. It is also possible that circulating mononuclear cells may transform or differentiate into osteoclasts (32).…”
Section: Discussionmentioning
confidence: 99%
“…We show that mobilization of cytoplasmic cAMP is likely one of the main mediators for PGE 2 activity since forskolin and the cAMP analogs, db-cAMP and 8-bromo-cAMP, could mimic the effect of PGE 2 Interestingly, cAMP induction decreases lipopolysaccharide (LPS)-and TNF-mediated NFkB-activation in a variety of experimental systems, resulting in reduced secretion of cytokines, including IL-12. [53][54][55][56][57][58][59] It is therefore tempting to speculate on the involvement of these 2 antagonistic pathways (both stress induced) in the regulation of DC differentiation. However, it is intriguing that the same PGE 2 signal that enhances TNF-␣-and IFN-␣-induced MoDC maturation simultaneously inhibits CD40L/E coliinduced cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies, which used cell-free systems, failed to demonstrate any effect of antiinflammatory steroids on PG production (1,3,4). Recently, however, evidence was obtained that glucocorticoids decrease PG production in different in vitro systems via inhibition ofphospholipase activity (5)(6)(7)(8)(9)(10)(11)(12)(13). Although this action of glucocorticoids seems to be fairly reproducible in in vitro systems, especially with high doses of steroids, almost no data are available on the effect of glucocorticoids on PG synthesis in vivo.…”
Section: Introductionmentioning
confidence: 99%